Ultrasound-assisted H2O2 degradation enhances the bioactivity of Schizophyllan for wound healing and tissue regeneration - He, Hui; Liu, Yu; Li, Qingpeng; Chen, Fenrou; Zhou, Lin (Frontiers in Pharmacology, 2025)
BackgroundSchizophyllan (SPG), a bioactive polysaccharide from Schizophyllum commune, possesses significant anti-inflammatory, antioxidant, and immunomodulatory properties. The molecular weight of polysaccharides significantly impacts their structural properties and biological functions. However, the functional characteristics of low molecular weight polysaccharides derived from Schizophyllum commune remain inadequately explored.MethodsThis study developed an ultrasound-assisted hydrogen peroxide (H2O2) degradation method to produce low-molecular-weight SPG with enhanced bioactivity. The process was optimized using response surface methodology, focusing on ultrasound duration, ultrasonic power, and H2O2 concentration. This approach effectively reduced the molecular weight of SPG from 4,409,608 Da to 257,500 Da, yielding three distinct variants: SPG-a (257,500 Da), SPG-b (429,300 Da), and SPG-c (364,800 Da). The bioactivity of these variants was assessed through in vitro cell proliferation and migration assays using BJ and HaCaT cells, as well as an in vivo zebrafish larval caudal fin regeneration model.ResultsIn vitro, SPG-b significantly promoted cell proliferation, increasing BJ and HaCaT cells growth by 53.69% and 14.59%, respectively, at a concentration of 300 μg/mL (p < 0.05), compared to undegraded SPG. Additionally, scratch assays revealed that SPG-a enhanced BJ cells migration by 24.13% (p < 0.05), while SPG-b exhibited most pronounced effect on HaCaT cells migration (17.12%, p < 0.05), compared to the undegraded SPG. In vivo, SPG-c (3.125 mg/mL) significantly improved fin regeneration rates by 6.97% (p < 0.05) in zebrafish larvae, compared to the undegraded SPG.ConclusionThis study demonstrates that ultrasound-assisted H2O2 degradation effectively reduces SPG molecular weight while enhancing its functional properties. These findings provide a foundation for the further development of SPG in pharmaceutical and cosmetic applications, highlighting its potential for broader utilization.